The Lineman's and Cableman's Handbook, Thirteenth Edition - Mack, James E.; Shoemaker, Thomas M. (McGraw-Hill Education, 2017)
The definitive guide to distribution and transmission line technology - fully revised for the latest standards. Thoroughly updated to reflect the 2017 National Electrical Safety Code ? (NESC?), this authoritative resource explains the principles and practices of electric transmission and distribution line construction, operation, and maintenance. You will get comprehensive coverage of the newest equipment, techniques, and procedures along with current OSHA, ANSI, and ASTM regulations. Throughout, detailed illustrations and photos make it easy to understand the material, and self-test questions and exercises reinforce key concepts.